واقع استخدام التكنولوجيا المالية في الوطن العربي - بن فضة, ويسام; بن حسان, حكيم (جامعة الوادي - University of Eloued, 2020)
من خلال هذه الدراسة سنعرض واقع استخدام التكنولوجيا المالية في الوطن العربي، مع إبراز التحديات التي تواجه دول الوطن العربي في تبني مبادئ التكنولوجيا المالية مع اقتراح بعض الحلول التي ستساهم في تفعيل استخدامها، بالاعتماد على المنهج الوصفي التحليلي لتلائمه مع طبيعة الموضوع، كما سندعم بحثنا بالإحصائيات عن واقع التكنولوجيا المالية على المستوى العالمي و على مستوى الوطن العربي. ولقد توصلنا إلى أن دول العالم قطعت أشواط كبيرة في هذا المجال رغم حداثته؛ كأمريكا والصين. في حين يعرف الوطن العربي نوع من التأخر رغم الجهود المبذولة لتوسيع استخدامها. ويرجع هذا لعدم ملائمة المناخ الاقتصادي والقانوني وكذا مقاومة الجهاز المالي للتغييرات الناجمة عن استخدام التكنولوجيا المالية. لذا وجب على الدول العربية توفير البيئة المناسبة للاستفادة من مزايا هذا المجال Through this study will try to offer realities of the use of financial technology in the Arab world and in Algeria in particular, highlighting the key challenges faced by Arab states to adopt the principles of financial technology, and suggest some solutions that will contribute to operationalization used it. This is study is based on the descriptive and analytical approach to suit the nature of the topic; we will also support our research with statistics and data on the reality of financial technology at the global level and at the level of the Arab world. We concluded that the world strides have been made in that area; Importantly, America and China. While known as the Arab world kind of delay despite efforts to expand the use of financial technology, that is due to inadequate economic climate, legal and financial system. So, the Arabian states have to provide the appropriate environment for this area to take advantage of benefits offered by.
The reality of the financial technology’s use in the Arabian world
مقال
Keywords: التكنولوجيا المالية ; الشركات الناشئة ; الوطن العربي